ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN DI PROVINSI MALUKU - Maryam Sangadji (Trunojoyo University of Madura, 2014)
Poverty is a classic problem faced by all regions. Maluku province is very highsequence to four of 33 provinces in Indonesia. This study aims to: (1) Determine theinfluence of education on poverty inMaluku (2) To analyze the health effects on povertyin Maluku (3) Determine the effect of public investment on poverty in Maluku; and (4)To analyze the influence of economic growth on poverty in Maluku. Quantitativeresearch using panel data regression model, the data collection process is primary orsecondary.The results showed that there were significant and negative influence of thevariables Education, Public Investment and economic growth on poverty in Malukuprovince, while the health variable positive effect on poverty in the province of Maluku.